Peran Teknologi dalam Peningkatan dan Efektivitas Proses Pembelajaran - Mubaroq, Muhammad Abror; Ilham, Muhammad Fakhri (Lembaga Yasin AlSys, 2023)
In this article, we focus on the role of technology in the development of education. The improvement and effectiveness of the learning process have become a primary focus in educational system development. In recent years, technological advancements have brought about significant changes in traditional learning processes. Access to digital resources, distance learning, interactive media, and online collaboration have enriched students' learning experiences and supported educators in delivering more effective instruction. Technology has also transformed the role of educators in the learning process. They are no longer just information providers but also facilitators and supporters of student learning. With the availability of technology, educators can access various learning tools and resources that enrich the classroom experience. They can utilize learning management platforms to organize materials, assignments, and assess student performance. Furthermore, technology enables educators to communicate with parents about their child's progress in school.